Law Enforcement on Corruption: A Case Study in Indonesia - Nawi, Syaharudin; Thalib, Hambali; Hafidz, Ma’ruf; Hambali, Azwad Rachmat; Ma'ruf, Tri Abriana (International Journal of Psychosocial Rehabilitation, 2020)
One of the violations of law that has been upsetting is the rise of corruption. Therefore, it is necessary to prevent and eradicate criminal acts in general as well as criminal acts of corruption in particular. This study aims to identify some issue to prevent and combat corruption. The method used in this study is descriptive by distributing a questionnaire to respondents consisting of some various components of society that have the potential to commit a criminal act of corruption. This study is expected to be an option in preventing the occurrence of corruption crime and also as an option in combating corruption. This study is subject to increase proper understanding for the citizens that impact on the creation of legal awareness, which creates a positive legal behavior for every citizen. This study found the high frequency of the corruption might increase in the future if not the right handling step. Factors occurrence that affects the corruption criminal in this study is the legal substance, legal structure, culture, legal awareness, facilities, and infrastructure. The judgment or verdict of judicial institutions at various levels against corrupt offenders has been considered unfair, and mild as well as incomparable to the acts committed by the suspects, so as not to give a deterrent effect. Steps of handling corruption to be overcome through the preventive (upstream) and repressive (downstream) steps taking into account the various issues. The steps should be taken to handle corruption through normative steps in the form of legislation and an empirical approach to local environmental conditions. Various concrete and constructive steps could overcome all factors that influence the occurrence of the corruption of a legal substance, legal structure, legal awareness, culture, and facilities and infrastructureKeywords: